A kaméleon pennájú Csokonai: (Szempontok a pályakép újraformálásához) - Debreczeni, Attila (Studia Litteraria, 2024)
In the past thirty years, there have been great changes in the philology and chronology of the Csokonai oeuvre. The consequences of which have to be applied to the whole oeuvre. This study aims to present the transformation of the fundamental aspects of interpretation. The basic groundwork for this is examining when and which works Csokonai intended to present to the public. The result of the analysis shows that the chameleon metaphor in the title not only means a multifaceted personality, but also the instinct with which Csokonai intended to adopt the cultural layers of his age, and thus representing its integrative character.